2017
DOI: 10.1007/s00296-017-3841-z
|View full text |Cite
|
Sign up to set email alerts
|

Muscular vasculitis confined to lower limbs: description of two case reports and a review of the literature

Abstract: Muscular involvement is common during systemic vasculitides, such as polyarteritis nodosa. However, in rare cases, muscular involvement can be the only clinically evident feature of the disease. The clinical pattern of isolated muscular vasculitis may mimic several other inflammatory muscle disorders, such as idiopathic inflammatory myositis, and may represent a challenge in differential diagnosis. Herewith, we present two clinical cases as examples of peculiar clinical and histopathological characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
10
1
Order By: Relevance
“…Muscle biopsy was performed in patients with myalgia who lacked a suitable visceral impairment site for biopsy, as well as a lower BVAS than other patients, suggesting that muscle biopsy would be useful as a definite diagnostic procedure even in the early phase of SVV and MVV. Muscular impairments of the lower limbs have been described as a localized and/or initial symptom of PAN [5,13,14], whereas the present study demonstrated that muscular vasculitis in the lower limbs could be a crucial early indication of MPA. To the best of our knowledge, only three cases of AAV have been reported in which muscular symptoms were the initial and main manifestation of disease and whereby definite diagnosis was made by muscle biopsy [15][16][17].…”
Section: Discussioncontrasting
confidence: 40%
See 3 more Smart Citations
“…Muscle biopsy was performed in patients with myalgia who lacked a suitable visceral impairment site for biopsy, as well as a lower BVAS than other patients, suggesting that muscle biopsy would be useful as a definite diagnostic procedure even in the early phase of SVV and MVV. Muscular impairments of the lower limbs have been described as a localized and/or initial symptom of PAN [5,13,14], whereas the present study demonstrated that muscular vasculitis in the lower limbs could be a crucial early indication of MPA. To the best of our knowledge, only three cases of AAV have been reported in which muscular symptoms were the initial and main manifestation of disease and whereby definite diagnosis was made by muscle biopsy [15][16][17].…”
Section: Discussioncontrasting
confidence: 40%
“…This supported that myalgia, similar to arthritis, may occur as the initial manifestation of PSV and that they may co-manifest [4]. Cases with muscular manifestations in the lower extremities, typically of the calf muscle, have been reported as muscular vasculitis related to PAN or PAN-mimicking disorders [5][6][7][8][9]13,14]. In our series of 21 patients with myalgia, the lower extremities were involved in all of them, and calf muscle pain was demonstrated in more than 80% of patients.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…We searched for case reports describing cases with both skin lesions and muscle disorders based on biopsy or medical imaging, and found five cases, including the case presented here (Table 1). [11][12][13][14] All cases had swelling, and we considered that the presence of swelling might be useful for differential diagnoses between CA with and without muscle disorders. Oral steroid therapy was not effective in two cases, including our case, and four cases, including our case, required immunosuppressants or intravenous methylprednisolone pulse therapy.…”
Section: Muscular Polyarteritis Nodosa (Mpan) Is a Concept Proposed Bymentioning
confidence: 99%